Penerapan Manajemen Even Pada Pengurus OSIS SMA N 3 Rambah Di Acara Futsal Liga Pelajar Rokan Hulu - Arisman Aris; Suhermon; Ferri Hendriyanto; Rani Zahra; Siska; Debby Indah; Tofikin; Hendri Mulyadi (JURNAL MASYARAKAT NEGERI ROKANIA, 2025)
This activity is located at SMA N 3 Rambah, Rambah District, Rokan Hulu Regency which has received accreditation B. Sports are a means to develop students' cognitive, affective, and psychomotor abilities. The purpose of this service is to provide insight to school student organization administrators in sports event management. The implementation time is in January 2025 at SMA 3 Rambah. The method in this study is a direct trial in the field. The number of participants is 18 students